Congenital neurosyphilis: yet a severe problem of public health - Menezes, Maria Luiza B; Marques, Carlos Alberto S; Leal, Tereza Maria A; Melo, Márcio C; Lima, Priscila R (Brazilian Journal of Sexually Transmitted Diseases, 2007)
Introduction: Syphilis is severe when it is transmitted from mother to child and invades the NSC. However, the correct diagnosis of congenital neurosyphilis (NCS) is a dilemma, because reagents syphilis’s tests in CRL are rare. As indirect criterion the minimum level of protein in CRL changed from 100 to 150 mg/dL, according to the Ministry of Health in Brazil, in 2003. Objectives: verifying congenital syphilis (CS) and CNS, studying the rate of false positive (FP) and true positive (TP) of last criterion and determine differences between titles of maternal and neonatal VDRL and clinical evolutions between FP e TP. Methods: secondary data of notified cases of CS and CNS from the Maternity of the University of Pernambuco - Northeast of Brazil, from June 1998 to June 2003, constituted the data and analysis bank by Epiinfo, version Windows 3.3.2. The two criteria of CNS were compared by analytic transversal and validation of diagnostic test studies, the FP and TP of the last criterion were verified and qui square were applied to determine differences between VDRL titles and neonatal occurrences between FP and TP. Results: 1,036 from 32,246 births (3.21%) had been diagnosed as CS, 360 (34.7%) had CNS by last criterion, 282 (27,2%) confirmed by new criterion (78,3% of last), representing 78 FP cases (21.7%). There were no significant differences (p > 0.05) between VDRL titles and occurrences (jaundice, infections, conjunctivitis and hypoxia) between FP and TP. Conclusion: CS, mainly CNS, continue like a severe problem oh public health.